2021
DOI: 10.3389/fnana.2021.670766
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Deprivation in Rats Decreases the Expression of Interneuron Markers in the Neocortex and Hippocampus

Abstract: Early life stress has profound effects on the development of the central nervous system. We exposed 9-day-old rat pups to a 24 h maternal deprivation (MD) and sacrificed them as young adults (60-day-old), with the aim to study the effects of early stress on forebrain circuitry. We estimated numbers of various immunohistochemically defined interneuron subpopulations in several neocortical regions and in the hippocampus. MD rats showed reduced numbers of parvalbumin-expressing interneurons in the CA1 region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…The reduction in PV + cellular density, observed in PrL is in line with the results of studies that employed a 3 h daily separation protocol during the first three postnatal weeks (Leussis et al, 2012;Ganguly et al, 2016;Grassi-Oliveira et al, 2016), as well as a previous result from our laboratory (Aksic et al, 2021). In another study, Helmeke et al (2008) reported an increase in the number of PV + neurons in the dorsal medial PFC of an adult Octogon degus which appeared strikingly opposite to our findings (Helmeke et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The reduction in PV + cellular density, observed in PrL is in line with the results of studies that employed a 3 h daily separation protocol during the first three postnatal weeks (Leussis et al, 2012;Ganguly et al, 2016;Grassi-Oliveira et al, 2016), as well as a previous result from our laboratory (Aksic et al, 2021). In another study, Helmeke et al (2008) reported an increase in the number of PV + neurons in the dorsal medial PFC of an adult Octogon degus which appeared strikingly opposite to our findings (Helmeke et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…There is also evidence suggesting that ELA, specifically MS, may have a delayed impact on PV cell density. Brains that were collected immediately (or within a few days) after ELA experience generally had no significant differences in PV levels compared to control-rearing (Giachino et al, 2007 ; Brenhouse and Andersen, 2011 ; Soares et al, 2020 ; Richardson et al, 2021 ), while brains collected later in life (in adolescence and/or P40 and older) generally had decreased PV levels (Leussis et al, 2012 ; Wieck et al, 2013 ; Ganguly et al, 2015 ; Lukkes et al, 2017 , 2018 ; Kim et al, 2020 ; Aksic et al, 2021 ). Since PV cells have been found to increase significantly in number from juvenility to adolescence in brain regions such as the PFC (Caballero et al, 2014 ; Wu et al, 2014 ), it is possible that ELA may inhibit the maturational time course of PV cells.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal deprivation models show usually impaired declarative memory and sensorimotor gating defects. Aksic et al (2021) reported a reduced number of RELN positive interneurons in the CA1 and CA3 regions of the hippocampus, but not in the neocortex. These anomalies were not caused by cell death, suggesting that maternal deprivation provokes a downregulation of RELN in offspring.…”
Section: Resultsmentioning
confidence: 97%
“… Aksic et al (2021) studied the effects of maternal deprivation in the expression of neocortex and hippocampus markers in P60 male and female rats. Maternal deprivation models show usually impaired declarative memory and sensorimotor gating defects.…”
Section: Resultsmentioning
confidence: 99%